Treatment with clobetasol propionate 0.025% topical therapy in various dermatoses - Guttedar, Ashwini; Mishra, Nitin; Gupta, Sanjay Kumar; Mohankar, Atul Dilip; Sancheti, Karan; Srivastava, Kanchan; Sharma, Puja; Gangwar, Ashok; Jain, Apoorva; Ganisetti, Lakshmi Sitara (International Journal of Research in Medical Sciences, 2021)
Owing to their anti-inflammatory and vasoconstrictive properties. Topical corticosteroids (TCs) provide benefits in various dermatological conditions, including atopic eczema, psoriasis, chronic hand eczema, and localized vitiligo. Clobetasol propionate (CP) is the most common topical agent possessing anti-inflammatory, antimitotic, antipruritic, and immunosuppressive properties that are employed in the management of plaque psoriasis. CP 0.025% cream was approved by the United States food and drug administration for the treatment of moderate-to-severe psoriasis in adult patients. The formulation is free from known contact allergens, such as propylene glycol, short-chain alcohols, and sorbitol-based emulsifiers, and has demonstrated hypoallergenic effects. High penetration of active ingredients and a lower degree of systemic absorption make CP 0.025% an effective and safe agent. This case series discusses the clinical experience of using CP 0.025% cream in various dermatologic conditions, focusing on its efficacy and safety.